2018
DOI: 10.1002/cncr.31599
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of overweight in long‐term survivors of childhood cancer after glucocorticoid treatment

Abstract: The results of the current study suggest that glucocorticoids used for the treatment of childhood cancer are not associated with long-term risk of overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
10
1
1
Order By: Relevance
“…Obesity is a well-recognized consequence of childhood ALL therapy among survivors treated with CRT [18, 19]; however, recent publications have highlighted the obesogenic nature of contemporary childhood ALL chemotherapy. In particular, prolonged exposure to corticosteroids has been linked to increased energy intake and weight gain during childhood ALL treatment [14, 20, 21], although the association between corticosteroids and long-term adiposity among survivors is not well-established [5, 22]. Other chemotherapeutic agents may contribute to adverse BMI profiles by adversely impacting energy expenditure by interfering with cardiovascular or motor-sensory function [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a well-recognized consequence of childhood ALL therapy among survivors treated with CRT [18, 19]; however, recent publications have highlighted the obesogenic nature of contemporary childhood ALL chemotherapy. In particular, prolonged exposure to corticosteroids has been linked to increased energy intake and weight gain during childhood ALL treatment [14, 20, 21], although the association between corticosteroids and long-term adiposity among survivors is not well-established [5, 22]. Other chemotherapeutic agents may contribute to adverse BMI profiles by adversely impacting energy expenditure by interfering with cardiovascular or motor-sensory function [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid use has also been associated with insulin resistance [48] and obesity [49], which are associated with diabetes development in non-cancer populations [50-52]. More recent data from the Swiss Childhood Cancer Study, however, found no evidence of a dose-response relationship between cumulative glucocorticoid dose and overweight in a cohort of 1,936 long-term childhood cancer survivors [53]. Further work is needed to better delineate the relationship between exogenous glucocorticoid use and diabetes risk in childhood cancer survivors.…”
Section: Diabetesmentioning
confidence: 99%
“…Other treatments were divided into glucocorticoids, anthracyclines, alkylating agents, and hematopoietic stem cell transplantation (HSCT). Glucocorticoid intake, including prednisone and/or dexamethasone, was estimated based on the cancer treatment protocols as described previously [ 37 ]. We also retrieved records on relapse during follow-up.…”
Section: Methodsmentioning
confidence: 99%